2011
DOI: 10.1093/jac/dkr208
|View full text |Cite
|
Sign up to set email alerts
|

Comparative effectiveness of continuing a virologically effective first-line boosted protease inhibitor combination or of switching to a three-drug regimen containing either efavirenz, nevirapine or abacavir

Abstract: Switching from a virologically successful first-line boosted PI-containing cART regimen to a non-nucleoside reverse transcriptase inhibitor-containing cART regimen containing either efavirenz or nevirapine is virologically safe, while switching to abacavir-containing cART should be avoided.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 30 publications
1
4
0
Order By: Relevance
“…Furthermore, subsequent therapeutic options were not compromised and both patients were eventually able to achieve optimal viral suppression, one while still on study treatment. The results presented herein are similar if not actually better than those of the French Hospital Database on HIV where the 12 months probability of virological failure was 3.7% in patients on a first‐line PI/r containing regimen [Bommenel et al, 2011]. The probability that virologic failure rate in the present study would be greater than that would not be surprising in that RADAR patients were treated with a median of 2 PI/r‐based treatment regimens for 5 years including 23.5% with a frank history of virologic failure.…”
Section: Discussionsupporting
confidence: 76%
“…Furthermore, subsequent therapeutic options were not compromised and both patients were eventually able to achieve optimal viral suppression, one while still on study treatment. The results presented herein are similar if not actually better than those of the French Hospital Database on HIV where the 12 months probability of virological failure was 3.7% in patients on a first‐line PI/r containing regimen [Bommenel et al, 2011]. The probability that virologic failure rate in the present study would be greater than that would not be surprising in that RADAR patients were treated with a median of 2 PI/r‐based treatment regimens for 5 years including 23.5% with a frank history of virologic failure.…”
Section: Discussionsupporting
confidence: 76%
“…As discussed above, triple-NRTI maintenance regimens in patients with no history of virological failure appeared to be non-inferior compared to standard two-class triple-(or even quadruple-) maintenance regimens, irrespective of whether these were PI-or NNRTI-based [48,66,70,72,73]. One observational study showed a higher risk of virological failure after switching to an ABC-based triple-NRTI regimen compared to the continued PI arm, however the triple-NRTI regimen in the cohort study was not always ABC/3TC/ZDV [69]. Furthermore, in routine clinical practice adherence to treatment may be lower than in the setting of RCTs.…”
Section: Discussionmentioning
confidence: 91%
“…From the French Hospital Database [64] a cohort study was performed in which selection was confined to HIV patients on their first-line virologically successful cART (HIV-1 RNA<500 copies/ml) with a ritonavir-boosted PI. Patients were selected who switched to cART composed of two NRTIs (3TC/ZDV in 64% of patients) plus EFV, NVP or ABC [69]. Each exposed patient was matched with three initially treatmentnaive patients who had not switched.…”
Section: Nrti-only Maintenance Compared To a Pi-based Regimenmentioning
confidence: 99%
“…Previous treatment failure on an NRTI‐containing regimen has been associated with an increased risk of virological failure when switching from a PI‐ to an NNRTI‐based regimen . A cohort analysis showed similar rates of virological failure at 12 months in PLWH switching from a first‐line PI/r to either efavirenz or nevirapine compared with continuing on the PI/r . If switching to nevirapine, consideration should be given to the risk of hypersensitivity reactions and hepatotoxicity.…”
Section: Supporting Individuals On Therapymentioning
confidence: 99%